Características agronômicas da mamoneira afetadas pelo método de condução de plantas e densidade de semeadura - Fioreze, Samuel Luiz; Lara-Fioreze, Ana Carolina da Costa; Pivetta, Laerte Gustavo; Rodrigues, João Domingos [UNESP]; Zanotto, Mauricio Dutra [UNESP] (GN1 Sistemas e Publicacoes, 2016)
The castor bean shows great potential for cultivation under the conditions found in Brazil, however, in order to achieve high productivity and introduce the crop into the Brazilian agricultural system, ever more efficient methods of crop management should be developed. The aim of this study was to evaluate the agronomic characteristics and productivity of the castor bean for the method of cultivation and planting density. The study was carried out under field conditions during the 2010 crop year, using the IAC 2028 cultivar. An experimental design of randomised blocks was employed in a 2 × 3 factorial, with four replications. The first factor comprised two planting densities (26,666 and 111,111 plants ha-1), while the second factor consisted of three methods of cultivation (control, partial pruning and thinning with pruning). At the end of crop development, the agronomic characteristics of the plants, yield components and productivity were determined. Pruning with thinning resulted in an improvement in the agronomic characteristics without affecting productivity, and reduced the crop cycle by 30 days. This behaviour, together with uniform maturation, may contribute to the mechanical harvesting of the crop, as well as allowing cultivation of the castor bean in the off-season without affecting the following harvest. Dense cultivation of the castor bean limited the appearance of secondary productive branches without affecting productivity, demonstrating a high phenotypic plasticity in crop development.
Agronomic characteristics of the castor bean as affected by cultivation method and planting density
Keywords: Productivity; Pruning; Ricinus cummunis L.; Thinning